Proximate composition of the mollusk Paxyodon syrmatophorus (Gmelin, 1791) (Bivalvia: Hyriidae) consumed on Tabatinga Island, Eastern Amazon (Research, Society and Development, 2020)
Fishing resources (e.g., fish, crustaceans and mollusks) make up the diet of populations, as they represent a source of protein. In this context, bivalve mollusks are of high ecological and socioeconomic importance, especially for communities that live along riverbanks. In this way, the present work registers the use of Paxyodon syrmatophorus as food by the native community of the island of Tabatinga, Abaetetuba, state of Pará, as well as, characterizes the centesimal composition of the mollusk. There were two types of preparation of the mollusk (scalded and stewed), always using simple seasonings in the cooking of the food. In addition, it was verified that the species presents a high moisture and protein content in its composition, with low lipid and calories, presenting in an average yield of the edible meat in 16.2%. It is concluded that the use of freshwater bivalves in the region is a source of subsistence for the inhabitants, who use their empirical knowledge in the organization of the preparation of P. syrmatophorus. Bivalve has a satisfactory centesimal composition and a complementary nutritional need. Studies on growth and reproduction are recommended to infer measures for sustainable resource management and subsequent use of shells.